Family Adaptability and Cohesion and High Blood Pressure among Urban African American women - Brittain, Kelly (2010)
African American women are at greater risk for complications related to high blood pressure. This study examined relationships between high blood pressure, pulse pressure, body mass index, family adaptability, family cohesion and social support among 146 Urban African American women. Significant relationships were found between family adaptability and systolic blood pressure (p = .03) and between adaptability and pulse pressure (p ≤ .01). Based on study results, practitioners should routinely assess family functioning, specifically family adaptability, in African American women who are at risk for high blood pressure or diagnosed with high blood pressure to minimize complications associated with hypertension.